THE CERAMICS OF THE INCA ADMINISTRATIVE CENTER OF TAMBO VIEJO - Valdez, Lidio M. (2014)
In this article we present the results of the analysis of the ceramic assemblage coming from Tambo Viejo, the single most important Inca establishment in the Acari Valley. Among others, this study reveals that at the time of the Inca conquest of Acari, there was a local ceramic style that already received some influence from the valleys found immediately to the north. With the Inca presence, the local style continued recei-ving northern influences, but also began incorporating new decorative elements, this time of Inca origins. Selected and previously modified Inca designs were incorporated. This evidence indicates that the Inca conquest of Acari did not represent the end of the local style; on the contrary, the local style survived to the point that Inca ceramics are rare in Tambo Viejo. This is more likely the result of the pacific incorpora-tion of Acari to Inca dominium. At the same time, the Inca occupation lasted only for a short period of time and thus did not result in a successful assimilation of the local cultural traits with deeper roots.